Applying Tissue and Mesh Combined Repair (TMC Repair) to Treat Adult Inguinal Hernia—A Study Based on 1,169 Cases - Chen, Lung-Fei (Frontiers in Surgery, 2022)
At present, the most widely favored technique for treating adult inguinal hernia is the use of tension-free mesh repair, while traditional means of tissue repair have been gradually phased out (Huang, 2010). Mesh repair seeks to prevent the occurrence of hernias by covering the entire myopectineal orifice with artificial mesh. Yet in doing so, it fails to reinforce the naturally weak area between the transversus abdominis arch and the iliopubic tract (Condon, 1989). To rectify this and reduce the chance of recurrence following inguinal hernia surgery, the author has combined mesh repair with autologous tissue repair to create a method called TMC repair (tissue and mesh combined repair). From Jan 1, 2010 to Dec 31, 2015 the author applied TMC repair to treat adult inguinal hernia in 1169 patients, achieving a recurrence rate of 0.68%. It is therefore a highly recommended method for treating adult inguinal hernia.